Sequential robust estimation for nonparametric autoregressive models. Issue 4 (1st October 2016) - Arkoun, Ouerdia; Pergamenchtchikov, Serguei
ABSTRACT: We construct a robust truncated sequential estimator for the pointwise estimation problem in nonparametric autoregression models with smooth coeﬃcients. For Gaussian models we propose an adaptive procedure based on the constructed sequential estimators. The minimax nonadaptive and adaptive convergence rates are established. It turns out that in this case these rates are the same as for regression models.